The reverberation signatures of rotating disc winds in active galactic nuclei - Mangham, SW; Knigge, C; Matthews, JH; Long, KS; Sim, SA; Higginbottom, N (Oxford University Press, 2017)
The broad emission lines (BELs) in active galactic nuclei (AGNs) respond to ionizing continuum variations. The time and velocity dependence of their response depends on the structure of the broad-line region: its geometry, kinematics and ionization state. Here, we predict the reverberation signatures of BELs formed in rotating accretion disc winds. We use a Monte Carlo radiative transfer and ionization code to predict velocity-delay maps for representative high- (C IV) and low-ionization (H α) emission lines in both high- and moderate-luminosity AGNs. Self-shielding, multiple scattering and the ionization structure of the outflows are all self-consistently taken into account, while small-scale structure in the outflow is modelled in the microclumping approximation. Our main findings are as follows: (1) The velocity-delay maps of smooth/microclumped outflows often contain significant negative responses. (2) The reverberation signatures of disc-wind models tend to be rotation dominated and can even resemble the classic ‘red-leads-blue’ inflow signature. (3) Traditional ‘blue-leads-red’ outflow signatures can usually only be observed in the long-delay limit. (4) Our models predict lag–luminosity relationships similar to those inferred from observations, but systematically underpredict the observed centroid delays. (5) The ratio between ‘virial product’ and black hole mass predicted by our models depends on viewing angle. Our results imply that considerable care needs to be taken in interpreting data obtained by observational reverberation mapping campaigns. In particular, basic signatures such as ‘red-leads-blue’, ‘blue-leads-red’ and ‘blue and red vary jointly’ are not always reliable indicators of inflow, outflow or rotation. This may help to explain the perplexing diversity of such signatures seen in observational campaigns to date.